Macromycetes of the Ojców National Park. I - Władysław Wojewoda (Acta Mycologica, 2014)
A floristic-ecological manograph of the macromycetes of the Ojców National Park (South Poland, Cracow-Wieluń Upland - Cracow Jurassic Region) is made. In this first part regional features of the investigated area and a list of 715 macromycetes are given. Some species are new to Poland, and 273 species are new to Cracow-Wieluń Upland.